Triggering Receptor Expressed on Myeloid Cells-1 Signaling: Protective and Pathogenic Roles on Streptococcal Toxic-Shock-Like Syndrome Caused by Streptococcus suis - Han, Li; Fu, Lei; Peng, Yongbo; Zhang, Anding (Frontiers in Immunology, 2018)
Streptococcus suis (S. suis) infections can cause septic shock, which is referred to as Streptococcal toxic-shock-like syndrome (STSLS). The disease is characterized by a severe inflammatory response, multiple organ failure, and high mortality. However, no superantigen that is responsible for Toxic Shock Syndrome was detected in S. suis, indicating that the mechanism underlying STSLS is different and remains to be elucidated. Triggering receptor expressed on myeloid cells (TREM) -1, belonging to the Ig superfamily, is an activating receptor expressed on myeloid cells, and has been recognized as a critical immunomodulator in several inflammatory diseases of both infectious and non-infectious etiologies. In this review, we discuss the current understanding of the immunoregulatory functions of TREM-1 on acute infectious diseases and then highlight the crucial roles of TREM-1 on the development of STSLS.